Two-dimensional digital photography for child body posture evaluation: standardized technique, reliable parameters and normative data for age 7-10 years - Stolinski, L. (Scoliosis Spinal Disord, 2017)
BACKGROUND: Digital photogrammetry provides measurements of body angles or distances which allow for quantitative posture assessment with or without the use of external markers. It is becoming an increasingly popular tool for the assessment of the musculoskeletal system. The aim of this paper is to present a structured method for the analysis of posture and its changes using a standardized digital photography technique. MATERIAL AND METHODS: The purpose of the study was twofold. The first one comprised 91 children (44 girls and 47 boys) aged 7–10 (8.2 ± 1.0), i.e., students of primary school, and its aim was to develop the photographic method, choose the quantitative parameters, and determine the intraobserver reliability (repeatability) along with the interobserver reliability (reproducibility) measurements in sagittal plane using digital photography, as well as to compare the Rippstein plurimeter and digital photography measurements. The second one involved 7782 children (3804 girls, 3978 boys) aged 7–10 (8.4 ± 0.5), who underwent digital photography postural screening. The methods consisted in measuring and calculating selected parameters, establishing the normal ranges of photographic parameters, presenting percentile charts, as well as noticing common pitfalls and possible sources of errors in digital photography. RESULTS: A standardized procedure for the photographic evaluation of child body posture was presented. The photographic measurements revealed very good intra- and inter-rater reliability regarding the five sagittal parameters and good reliability performed against Rippstein plurimeter measurements. The parameters displayed insignificant variability over time. Normative data were calculated based on photographic assessment, while the percentile charts were provided to serve as reference values. The technical errors observed during photogrammetry are carefully discussed in this article. CONCLUSIONS: Technical developments are allowed for the regular use of digital photogrammetry in body posture assessment. Specific child positioning (described above) enables us to avoid incidentally modified posture. Image registration is simple, quick, harmless, and cost-effective. The semi-automatic image analysis, together with the normal values and percentile charts, makes the technique reliable in terms of child’s posture documentation and corrective therapy effects’ monitoring. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13013-017-0146-7) contains supplementary material, which is available to authorized users.